IMPLEMENTATION OF MICRO BUSINESS PRODUCTIVE ASSISTANCE POLICY IN PANGKALAN VILLAGE LANGKAPLANCAR DISTRICT PANGANDARAN REGENCY IN 2021 - Alis Gusmianti; Agus Dedi; Dini Yuliani (JGSRD: Journal of Government Science and Rural Development, 2023)
This research is motivated by the still not optimal implementation of the Micro Business Productive Assistance policy in Pangkalan Village, Langkaplancar District, Pangandaran Regency in 2021. The research method used in this study is qualitative. In this study, primary data are direct and immediate data that can be obtained from the source. The data sources used in this study were 8 informants consisting of the Village Head, Village Secretary, General Affairs Officer, Community Leaders, Youth Leaders, and Community Representatives. The data collection in this research is data collection with observation methods and in-depth interviews and documentation. Based on the results of research and discussion that the implementation of the Micro Business Productive Assistance policy in 2021, namely the lack of coordination between the Office of Cooperatives for Micro, Industry and Trade and the Village Government resulted in a lack of clear information on the program implementation flow, as well as the absence of formal media in conveying information to the public causing the delivery of information to the community. Information only relies on informal activities carried out by the Village Government directly to the community. The steps taken by the Village Government in dealing with these obstacles are that the Village Government maximizes the process of delivering information directly to the target community even though it is not accompanied by formal information media, and the Village Government asks for information on the causes of policies that are not well targeted in the Productive Assistance for Micro Business in 2015. 2021 in anticipation of complaints that will be obtained from people who feel aggrieved.